THE MOSAIC OF SINGLE WINDOW FOR TRADE - Nikiforovich Sidorov, Víctor (2024)
In a constantly evolving global trade context, «single window» systems have become key tools for simplifying and optimizing commercial processes. These systems play a crucial role in streamlining and automating the interaction between businesses and government authorities, allowing for the exchange of information and compliance with regulatory requirements through a single interface. However, practical experience shows that approaches to implementing the «single window» concept vary significantly based on the characteristics and needs of different economies. This article explores the diversity of existing single window systems and their impact on simplifying commercial operations. It places particular emphasis on two main types of single window systems: (i) those oriented towards importers and exporters, and (ii) those related to the transportation of goods. The discussion highlights the importance of interaction platforms in trade, which ensure the integration of commercial and transportation procedures on a global scale. Finally, a documentary methodology was used along with a legal doctrinal approach.